Long-term follow-up after multiple plastic stenting for refractory pancreatic duct strictures in chronic pancreatitis - Tringali, Andrea; Bove, Vincenzo; Vadalà di Prampero, Salvatore F.; Boškoski, Ivo; Familiari, Pietro; Perri, Vincenzo; Costamagna, Guido (Endoscopy, 2019)
Background Dominant pancreatic duct strictures in chronic pancreatitis are often managed by endoscopic placement of a single plastic stent. Insertion of multiple plastic stents (MPS) has been proven to be effective in managing refractory strictures, but data are still limited. The aim of this study was to investigate the efficacy and long-term results of MPS to dilate pancreatic duct strictures in chronic pancreatitis.Methods 48 patients (34 men; mean age 44 years) with chronic pancreatitis and a single pancreatic stent through a refractory stricture in the pancreatic head underwent the following protocol: 1) removal of the single pancreatic stent; 2) balloon dilation of the stricture; 3) insertion of the maximum number of stents; 4) stent removal after 6 – 12 months. Results The median number of pancreatic plastic stents placed was 3 (diameter 7 – 11.5 Fr, length 3 – 7 cm). Five patients (10.4 %) had persistent strictures after MPS removal. During a mean follow-up of 9.5 years (0.3 – 15.5 years) after stent removal, 74.4 % (32/43) of the patients were asymptomatic, and 25.6 % (11/43) experienced pancreatitis recurrence or pancreatic type pain after a mean time of 26.4 months (8/43, 18.6 % underwent plug extraction without evidence of stricture recurrence; 3/43, 7.0 % had stricture recurrence). No major complications were recorded.Conclusion Endoscopic multiple plastic stenting of chronic pancreatitis-related pancreatic duct strictures showed satisfactory long-term results, with the option of re-treatment. This procedure can be considered an important therapeutic alternative for painful pancreatic duct strictures located in the head of the pancreas in the setting of chronic pancreatitis.